1997
DOI: 10.1007/s001670050047
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the scapholunate ligaments in acute wrist trauma - arthroscopic diagnosis and minimally invasive treatment

Abstract: The final result of the treatment of distal intra-articular radius fractures depends both on the accuracy of the fracture reduction and on the presence of additional carpal injuries. In particular, lesions of the intrinsic ligaments usually lead to severe degenerative damage of the wrist joint if they are missed primarily. With the introduction of wrist arthroscopy, these tears can be evaluated and treated earlier. Since 1993 arthroscopically assisted treatment has been performed in 23 patients with distal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
13

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
1
23
0
13
Order By: Relevance
“…Recent reports have described associated tears of the triangular radioulnar ligament in up to 53% and of the scapholunate ligament in up to 21% of extra-and intraarticular fractures of the distal radius. [33][34][35] It has been suggested that these injuries were responsible for poor results unless they were diagnosed and treated early, but their clinical significance is not entirely clear. We believe that minor tears of the intercarpal ligaments do not lead to significant instability and heal without further treatment, provided that the anatomy of the joint, including the distal radioulnar joint, is meticulously restored and undue traction with external fixation devices is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have described associated tears of the triangular radioulnar ligament in up to 53% and of the scapholunate ligament in up to 21% of extra-and intraarticular fractures of the distal radius. [33][34][35] It has been suggested that these injuries were responsible for poor results unless they were diagnosed and treated early, but their clinical significance is not entirely clear. We believe that minor tears of the intercarpal ligaments do not lead to significant instability and heal without further treatment, provided that the anatomy of the joint, including the distal radioulnar joint, is meticulously restored and undue traction with external fixation devices is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53][54][55][56] Rates when diagnosed radiographically range from 13.3% to 29%. [57][58][59][60][61][62] Mudgal and Hastings suggest the mechanism of this combined injury can be attributed to a combination of tensile stress in ulnar deviation and axial (compression) stress in either radial or ulnar deviation.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 99%
“…It is especially effective in young patients suffering from distal intraarticular radius fractures when the reduction and fracture treatment can be performed under arthroscopic assistance. At the same time, lesions of the TFCC (triangular fibrocartilage complex) and of the intrinsic ligaments can be evaluated and treated under arthroscopic view as known from Adolfson (1994), Cooney et al (1990), Dautel et al (1993), Fellinger et al (1995), Knopp et al (1988), and Peicha et al (1997).…”
Section: Introductionmentioning
confidence: 99%